PENGARUH PUPUK DAUN GREEN-TAMA DAN ZPT ATONIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicum esculentum Mill) VARIETAS BERLIAN - Marisi Napitupulu, Melani Febriantini, Akas Pinaringan Sujalu, (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2013)
Objectives of the research were to study the effect of Green-Tama fertilizer and Atonik plant regulator, as well as their interaction on the growth and production of tomato; and to find proper dosage of Green-Tama fertilizer and proper consentration of Atonik plant regulator for better growth and production of tomato.The Completely Randomised Design was employed for this research with factorial 3 x 3 and 3 replications.  The first factor was Green-Tama fertilizer dosage (K), consisted of 3 sub factors: no Green-Tama fertilizer application (k0), 2 ml l-1 water (k1), and 3 ml l-1 water (k2). And the second factor was Atonik plant regulator concentration (P) that consisted of 3 sub-factors: no Atonik plant regulator application (p0), 1 ml l-1 water (p1, and 2 ml l-1 water (p2).Results of the research revealed that:1. The Green-Tama fertilizer affected very significantly on the plant height at 4 weeks after sowing, days of crop firstly flowered and weight per fruit, affected significantly on plant height at 6 weeks after sowing, and did not affect significantly on plant height at 8 weeks after sowing and number of fruit per crop;2. The Atonik plant regulator concentration affected very significantly on the plant height at 4, 6, and 8 weeks after sowing, days of crop firstly flowered, number of fruit per crop, and fruit weight per crop, and did not affect significantly on plant height at 2 weeks after sowing;  and3. The interaction between those two factors did not affect significantly on all parameters observed.